Technical performance analyses in elite Paralympic swimming using wearable technology: two case studies - Slopecki, M.; Charbonneau, M.; Deguire, S.; Côté, J. N.; Clément, J. (Sports Biomechanics, 2025)
We present two case studies that make use of wearable technology to provide performance indicators on optimal swim stroke techniques in breaststroke (case 1) and freestyle (case 2). In the first case study, we present and use a novel metric, the velocity variation score, to maximise breaststroke technical performance for an athlete with Achondroplasia Dwarfism, by comparing their normal technique to two alternates, focused on 1) fast arm sculling and 2) high stroke rate (HSR). We observed lower velocity variation scores using the adapted breaststroke techniques (p < 0.001), the HSR technique had the lowest velocity variation score (p < 0.001). In the second case, we determine the optimal breathing strategy, breathing to the impaired or unimpaired side, for an athlete with a unilateral hand impairment performing freestyle swimming. Results showed that the forward velocity was significantly lower in the left-to-right stroke cycle transition and right (arm pull) when breathing to the impaired (left) side. To varying degrees, these cases demonstrate that wearable-based intra-stroke analyses can provide individualised technique recommendations that benefit competitive race peformance.